VEGF Trap-Eye for macular oedema secondary to central retinal vein occlusion: 6-month results of the phase III GALILEO study. Issue 3 (7th January 2013) - Holz, Frank G; Roider, Johann; Ogura, Yuichiro; Korobelnik, Jean-François; Simader, Christian; Groetzbach, Georg; Vitti, Robert; Berliner, Alyson J; Hiemeyer, Florian; Beckmann, Karola; Zeitz, Oliver; Sandbrink, Rupert
Abstract : Aim: To evaluate intravitreal VEGF Trap-Eye (VTE) in patients with macular oedema secondary to central retinal vein occlusion (CRVO). Methods: In this double-masked study, 177 patients were randomised (3:2 ratio) to intravitreal injections of VTE 2 mg or sham procedure every 4 weeks for 24 weeks. Best-corrected visual acuity was evaluated using the Early Treatment Diabetic Retinopathy Study chart. Central retinal thickness (CRT) was measured with optical coherence tomography. Results: From baseline until week 24, more patients receiving VTE (60.2%) gained ≥15 letters compared with those receiving sham injections (22.1%) (p<0.0001). VTE patients gained a mean of 18.0 letters compared with 3.3 letters with sham injections (p<0.0001). Mean CRT decreased by 448.6 and 169.3 µm in the VTE and sham groups (p<0.0001). The most frequent ocular adverse events in the VTE arm were typically associated with the injection procedure or the underlying disease, and included eye pain (11.5%), increased intraocular pressure (9.6%) and conjunctival haemorrhage (8.7%). Conclusions: VTE 2 mg every 4 weeks was efficacious in CRVO with an acceptable safety profile. Vision gains with VTE were significantly higher than with observation/panretinal photocoagulation if needed. Based on these data, VTE may provide a new treatment option for CRVO.